The Hijab as The Identity of Muslim Women: An Analysis of Sayyid Muhammad Alawi al-Maliki’s Thought in Ādāb al-Islām fī Niẓām al-Usrah - Qurrotul A'yuni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The hijab carries multiple meanings, representing spirituality, societal expectations, and political identity. However, Sayyid Muhammad Alawi al-Maliki regards the hijab as a normative obligation that reflects moral and spiritual values, capable of shaping a women-friendly social order. This study aims to present a new perspective on the obligation of hijab by examining the interpretation of Sayyid Muhammad Alawi al-Maliki, with particular attention to the construction of his arguments grounded in Islamic moral and spiritual values. This study adopts a qualitative approach utilizing a library-based research method, in which data are systematically analyzed through content analysis. The primary source of data is Al-Maliki’s work titled Adabul Islam fi Nizamil Usrah, while secondary sources include books, works of classical and contemporary scholars, and journal articles related to the research theme. Findings indicate that al-Maliki understands hijab not merely as a religious obligation, but as part of a social transformation process that strengthens the status and dignity of women within Islamic society. The hijab serves not to isolate women, but to foster environments in which their contributions may flourish without the encumbrance of sexual objectification or social marginalization. His ideas serve as a critical response to Western views that problematize the hijab, by promoting a historical-theological approach rooted in authentic hadiths. This study offers a fresh perspective by examining the hijab discourse through spiritual and social dimensions, as interpreted in Al-Maliki’s thought.